Emotional Geographies Experienced by an Indonesian Doctoral Student Pursuing her PhD in New Zealand during the COVID-19 Pandemic - Taloko, Johanes Leonardi; Putra, Martin Surya; Hartanto, Yenny (Journal of International Students, 2020)
This narrative study explores the emotional experience of a female Indonesian pursuing her PhD in New Zealand when the COVID-19 pandemic hit this country. Garnered from the results of several virtual interviews with the participant, the data were analysed with the Hargreaves‟s emotional geography framework (2001) focusing on five different emotional dimensions: physical, sociocultural, moral, professional, and political. The findings showed that during the COVID-19 pandemic impacted PhD study, the participant experienced different emotions shaped by physical, sociocultural, moral, professional, and political factors while negotiating and coping with such emotions.